2019
DOI: 10.3389/fbioe.2019.00278
|View full text |Cite
|
Sign up to set email alerts
|

Sub-millisecond Control of Neuronal Firing by Organic Light-Emitting Diodes

Abstract: Optogenetics combines optics and genetics to enable minimally invasive cell-type-specific stimulation in living tissue. For the purposes of bio-implantation, there is a need to develop soft, flexible, transparent and highly biocompatible light sources. Organic semiconducting materials have key advantages over their inorganic counterparts, including low Young's moduli, high strain resistances, and wide color tunability. However, until now it has been unclear whether organic light emitting diodes (OLEDs) are cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…We and others have previously shown that OLEDs provide ample brightness to control neurons both in culture and in Drosophila melanogaster larvae. [11][12][13] In this contribution, we introduce a microstructured OLED array and show that it can be used to test and develop new hypotheses about neural systems by providing highly controlled local photo-stimulation. We apply the device to study the response of Drosophila melanogaster larvae to local excitation and inhibition of the peripheral sensory system.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that OLEDs provide ample brightness to control neurons both in culture and in Drosophila melanogaster larvae. [11][12][13] In this contribution, we introduce a microstructured OLED array and show that it can be used to test and develop new hypotheses about neural systems by providing highly controlled local photo-stimulation. We apply the device to study the response of Drosophila melanogaster larvae to local excitation and inhibition of the peripheral sensory system.…”
Section: Introductionmentioning
confidence: 99%
“…3, 4 and Supplementary Movie 3). While OLEDs can heat up when driven at high currents for extended times, a worst-case estimate (no heat dissipation, all electrical power converted to heat) shows that surface temperatures in our experiment will not have risen by more than 3.4°C; previous studies have measured a 1.1°C increase in temperature for similar light intensity levels but inferior OLED performance 15 . Thus, it is highly unlikely that heating caused the observed response in control larvae.…”
Section: Resultsmentioning
confidence: 50%
“…We and others have previously shown that OLEDs provide ample brightness to control neurons in culture, in Drosophila melanogaster larvae and very recently in vivo [13][14][15][16] . In this contribution, we introduce a microstructured OLED array and show that it can be used to test and develop new hypotheses about neural systems by providing highly controlled local photostimulation.…”
mentioning
confidence: 99%
“…Mccall and colleagues have made cellular-scale microscale, inorganic light-emitting diodes (μ-ILED, 6.45 μm thick, 50 × 50 μm 2 ), and the μ-ILED is transferred to Polyethylene terephthalate (PET, polyester film) substrate for long-term implantation [ 32 ]. The thickness of organic light-emitting diodes (OLED) can even be less than 1 μm, which is more suitable for implantation in the brain [ 33 ]. Therefore, we can combine flexible electrode and optical interface to explore long-term optogenetic modulation and multi-mode sensor integration in the future [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%